Analisis Yuridis Terhadap Pembelian Unit Hunian yang Mengandung Obscuur Libel Berdasarkan Putusan No. 200/Pdt.G/Pn.Jkt.Utr - R Robinson; Krisdayanti Sirait; Pebi Gresia Br Manjorang; Febiola Br. Ginting (Jurnal Interpretasi Hukum, 2024)
A residential unit is a unit of a house or dwelling that is used as a shelter and residence for humans. Residential units include various shapes and sizes designed to meet the needs of individuals or groups. This residential unit shows the importance of fair and inclusive housing policies so that all levels of society have access to decent, safe, and comfortable housing, and encourages equitable infrastructure development throughout the region. The process of purchasing a residential unit requires important procedures to ensure that transactions between consumers and developers are clear and safe. The researcher uses an empirical legal research method. This method refers to legal provisions and the application of regulations to problems that occur in the field. This study uses data sourced from a descriptive analytical Literature Study. The results of the study show that there are many things that need to be reviewed by consumers and developers before making an agreement. This aims to avoid the emergence of default by the parties. In this context, default occurs when one party does not fulfill the agreed obligations, either in whole or in part, or fulfills the obligations in a manner that is not in accordance with the provisions of the agreement. The results of this study also show that the lawsuit filed is an Obscuur Libel lawsuit, namely a lawsuit that is unclear, vague and contrary to the formal requirements in the provisions of legal procedures. Because of its hidden or vague nature, this can be a challenge in proving in court, because it requires further interpretation as to whether the information is indeed detrimental. This term is often used in the context of criminal or civil law to describe a form of dissemination of information that is detrimental to someone, but the method of dissemination is not direct or open.